Association of large scale 4977-bp "common" deletions in sperm mitochondrial DNA with asthenozoospermia and oligoasthenoteratozoospermia - Prafulla S Ambulkar; Ajay R Chuadhari; Asoke K Pal (Wolters Kluwer Medknow Publications, 2016)
OBJECTIVE: To determine the association of large-scale mitochondrial DNA (mtDNA) deletions with abnormal sperm or abnormal flagellar movement of human spermatozoa in asthenozoospermia and oligoasthenoteratozoospermia (OAT) subjects using percoll gradients fractionation and long-range polymerase chain reaction (PCR). DESIGN: We investigated sixty infertile men and thirty normal healthy fertile controls. Of sixty infertile men, 39 were asthenozoospermia and 21 were OAT. MATERIALS AND METHODS: Percoll gradients discontinuous technique was used for separation of spermatozoa on the basis of their motility. Long-range PCR was used for detection of "common " 4977-bp deletions, and primer shift technique was used for confirmation of deletions. RESULTS: Overall fourteen subjects (14/60; 23.3%) of which eight (8/39; 20.5%) asthenozoospermia and six (6/21; 28.6%) OAT had shown deletions of 4977-bp. Deletions were more common (23.3%) in 40% fraction than 60% (11.6%) and 80% (5%) fractions. Sequencing results had shown deleted region of mtDNA. CONCLUSION: Abnormal spermatozoa had more number of mtDNA deletions than normal sperm, and abnormal spermatozoa had lost genes for the oxidative phosphorylation. Our findings suggest that large-scale 4977-bp mtDNA deletions in the spermatozoa from the infertile subjects cause the asthenozoospermic and OAT pathophysiological conditions in infertile males.